Reciprocity in Diversity : Doing Collaborative Research with Afro-Diasporic Communities - Gruber, Valerie (2021)
Academic knowledge production continues to marginalize voices of minoritized majorities, while privileging those of majoritized minorities. At the core of this exclusionary practice are moral questions of whose knowledge counts as right, valid and legitimate. How can researchers share their power of definition with communities structurally excluded from academia, but directly affected by the results of academic knowledge production? Which kind of spaces and institutional settings allow for an inclusive and collaborative research process that enables mutual learning and empowerment? To provide some answers to these questions, I give insights into an ongoing process of participatory research-creation developed with Afro-diasporic communities from Brazil and Colombia. Thereby, an artistic meta-language co-created with different community actors and artists enables the participants to relate to each other through and beyond diversity. Although huge challenges arise with regard to institutional boundaries, impact measurement and translatability, the project confirms that it is possible to produce valid and mutually beneficial knowledge in collaboration with marginalized communities. Apart from solidarity, however, such a relational research process requires the co-creation of a space for mutual learning based on human equality, dignity and reciprocity.